Progress and Pitfalls in Women's Education in Turkey (1839-2017) - (:unkn) unknown (QUEENS UNIV, FAC EDUCATION, 2018)
Girls' education and women's enlightenment have been key elements of the Kemalist Republic (1923), which claimed to face towards the highest level of civilization and treated women as the symbols of a modernized secular Turkish nation-state and society. However, the official ideological and cultural principles of the education system in Turkey underwent dramatic transformations. Education policies under the AKP rule have been shaped by a combination of neoliberalism, conservatism and Islamism. Consequently, the education system has changed rapidly especially during the last six years. Since early 2012, Turkish education system suffered radical changes with tremendous implications for women's education in particular and gender equality in general. In this article, after a general review and commentary about the development of women's education during the different stages of the Republic, we will concentrate on the process of Islamization of education in recent Turkey especially concerning consequences for girls and women. This brings along the need for a closer look on the clerical schools, so called Imam Hatip Schools in which apart from the conventional High School Curriculum Islamic teachings is provided to students.
Keywords: Women's Education; Turkey; Gender Equality; Islamization of education; GIRLS